EVALUASI KETERLAMBATAN PENGIRIMAN PAKET DENGAN MENGUNAKAN METODE SIX SIGMA DPMO PADA DIVISI LAST MILE DELIVERY PT SATRIA ANTARAN PRIMA.TBK CABANG SURABAYA - Yakin, Muhamad Anggi Ainul; Kirono, Indro (Jurnal Baruna Horizon, 2025)
Abstract. The purpose of this study is to evaluate the delay in package delivery in the Last Mile Delivery Division of PT Satria Antaran Prima Tbk Surabaya Branch using the Six Sigma method, especially the DPMO (Defects Per Million Opportunities) approach. Logistics sees late delivery as a major problem that affects customer satisfaction and company reputation. To find and analyze the causes of delays, the SIX SIGMA method is used. Shipping data for the last six months were collected and analyzed to calculate the DPMO value. The results of data processing using the sigma method show 3 types of failures in re-delivery, misdirection and re-delivery reviewed from shipping data for 6 months January - June 2024, a total of 415,150 packages, the number of failed deliveries was 8,213, CTQ (critical to quality) owned is 1. The DPMO value is 19.783 so that the SIGMA value is 2.4. based on the SIGMA calculation shows a result of 2.4 which means statistically only 2.4 defects occur per million opportunities, This means almost perfect quality.